Analytical investigation of a light weight tall structure considering lateral load resisting system using analytical tool ETABS - Kumar, Amit; Bajaj, Rachana M; Soni, Kapil (International Journal of Scientific Research in Civil Engineering, 2020)
Strong structures are slanted to quake in view of mass of the structures. fundamental usage of assistant lightweight concrete (SLWC) is to diminish the dead pile of a strong structure, which empowers the essential fashioner to lessen the range of the fundamental people like column, fragment, and footings which brings about abatement of seismic quake powers on the structure. This assessment is an undertaking to envision the seismic response of a ten-celebrated invigorated strong packaging with the usage of lightweight concrete. A particularly arranged ten story point of reference is taken for study. The structure is exhibited with ETABS programming, and assessment is finished with average weight and lightweight concrete. The basic justification of our examination is to apportion a light weight concrete in a tall structure, where we can check its positive and negative effect on the quality of the structure. In like manner to legitimize the assistant cost decline due to utilization of light weight material.
Keywords: ETABS; Structural Analysis; Forces; Cost Analysis; Lateral Forces; Displacement